Continued Chemotherapy After Concurrent Chemoradiotherapy Improves Treatment Outcomes for Unresectable Cutaneous Squamous Cell Carcinoma: An Analysis of 13 Cases - Hiura, Azusa; Yoshino, Koji; Maeda, Takuya; Nagai, Kojiro; Oaku, Satoe; Yamashita, Chisato; Kato, Megumi; Uehara, Jiro; Fujisawa, Yasuhiro (Frontiers in Medicine, 2019)
Background There is no standard systemic therapy for unresectable cutaneous squamous cell carcinoma (ucSCC), although various chemotherapy regimens have been reported. In our department, concurrent chemoradiotherapy (CCRT) for ucSCC resulted in a 1-year survival rate similar to that of resectable cutaneous squamous cell carcinoma (cSCC). Treatment involves continued chemotherapy after CCRT. Here, we report the importance of continued chemotherapy after CCRT, based on treatment outcomes. Patients and methods We retrospectively evaluated 13 patients with ucSCC, assessing the overall survival, overall response rate (ORR), and disease control rate (DCR). Results CCRT with continued chemotherapy resulted in an ORR of 84.6%, DCR of 92.3%, and 1-year survival rate of 75%. Of the 13 patients treated with CCRT with continued chemotherapy, 6 had no metastasis. The remaining 7 patients developed metastasis to other organs or lymph nodes beyond the regional lymph nodes, although most sites of metastasis were outside the irradiation area. Conclusion We conclude that CCRT with continued chemotherapy was effective in treating the irradiation site (primary lesion and regional lymph nodes) and any organ metastasis, although, it is unclear for how long the treatment remains effective.